2019
DOI: 10.3390/molecules24173178
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Study of DNA-Recognized Peptide Compound Pyrrole-Imidazole Polyamide Targeting Human TGF-β1 Promoter for Progressive Renal Diseases in the Common Marmoset

Abstract: Pyrrole-imidazole (PI) polyamides are novel gene silencers that strongly bind the promoter region of target genes in a sequence-specific manner to inhibit gene transcription. We created a PI polyamide targeting human TGF-β1 (hTGF-β1). To develop this PI polyamide targeting hTGF-β1 (Polyamide) as a practical medicine for treating progressive renal diseases, we examined the effects of Polyamide in two common marmoset models of nephropathy. We performed lead optimization of PI polyamides that targeted hTGF-β1 by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…We recently developed a PI polyamide to target human TGF-β1 and examined this PI polyamide in a primate model of cyclosporine A-induced nephropathy and unilateral urethral obstruction in the common marmoset, which has high gene homology of 90% to the human TGF-β1 gene. The human TGF-β1 PI polyamide effectively improved these nephropathies in the common marmoset [27]. We will, therefore, create diabetic mellitus in the common marmoset with STZ, and examine the effectiveness of human TGF-β1 PI polyamide as a preclinical study for the treatment of diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…We recently developed a PI polyamide to target human TGF-β1 and examined this PI polyamide in a primate model of cyclosporine A-induced nephropathy and unilateral urethral obstruction in the common marmoset, which has high gene homology of 90% to the human TGF-β1 gene. The human TGF-β1 PI polyamide effectively improved these nephropathies in the common marmoset [27]. We will, therefore, create diabetic mellitus in the common marmoset with STZ, and examine the effectiveness of human TGF-β1 PI polyamide as a preclinical study for the treatment of diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the binding of PI polyamide was reported to alter the conformation of double-stranded DNA promoter construction and impair target promoter activity [ 19 ]. We also reported that PI polyamides targeting the TGF-β1 promoter improved TGF-β1-induced fibrotic diseases such as progressive renal diseases [ 20 ], diabetic nephropathy [ 21 ], hypertrophic scar in marmoset [ 15 ], restenosis of arteries after injury [ 22 ], encapsulating peritoneal sclerosis [ 23 ], and suppressed dimethylnitrosamine-induced liver fibrosis [ 24 ]. In addition, pyridine derivative that inhibits TGF-β production improve HCV-related fibrosis and inflammation [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, we did not confirm inhibition of cancer progression via TGF-β1 suppression by GB1101 in protein level. However, we previously reported the GB1101 effects on various types of diseases such as nephropathy [ 20 ], hypertrophic scar [ 15 ], restenosis of arteries after injury [ 22 ], peritoneal sclerosis [ 23 ], and liver fibrosis [ 24 ] using rat or marmoset models. Therefore, the perspective of this study is to evaluate whether GB1101 would actually be available to cancer therapy by in vivo study.…”
Section: Discussionmentioning
confidence: 99%
“…For histopathological assay, the sections were stained with hematoxylin-eosin (H&E) to observe pathological changes or Masson’s trichrome to evaluate collagen deposition. Renal pathological changes and collagen deposition were estimated by professionals using morphometric methods [ 33 ]. For IF assay of renal tissue, the sections were blocked with normal goat serum for 30 min, and then stained with primary antibodies of α-SMA, Col1A, or a mixture of Cpt1a and Twist1, respectively.…”
Section: Methodsmentioning
confidence: 99%